2012
DOI: 10.1007/s12262-012-0609-2
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Perforation Peritonitis in Delhi: 77 Cases Experience

Abstract: Perforation peritonitis is the most common surgical emergency encountered by surgeons all over the world as well in India. The spectrum of etiology of perforation peritonitis in tropical countries continues to differ from its western counterpart. This study was conducted at Hindu Rao Hospital, Municipal Corporation of Delhi, New Delhi, India, designed to highlight the spectrum of perforation peritonitis in the eastern countries and to improve its outcome. This prospective study included 77 consecutive patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 27 publications
5
40
0
2
Order By: Relevance
“…who reported majority of them being in age group of 35-45 years. Mean age in our study was 30 which was comparable to that Yadav et al 6 , who reported the mean age to be 33.9 yrs. Males were seen to predominate in incidence in all the studies [6][7][8] .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…who reported majority of them being in age group of 35-45 years. Mean age in our study was 30 which was comparable to that Yadav et al 6 , who reported the mean age to be 33.9 yrs. Males were seen to predominate in incidence in all the studies [6][7][8] .…”
Section: Discussionsupporting
confidence: 88%
“…Mean age in our study was 30 which was comparable to that Yadav et al 6 , who reported the mean age to be 33.9 yrs. Males were seen to predominate in incidence in all the studies [6][7][8] . The highest male preponderance was noticed by Jhobtaet al 7 , where the ratio of male to female was 5.2:1, followed by Yadav et al6 where the ratio was 4.9:1, which was almost similar to our study in which the ratio was 5.6:1.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Suture sinus occurred more frequently with nylon suture because of its long memory and stiff nature. Sinus formation occurred less frequently with the use of PDS because it had been found to be smooth, pliable and minimal memory (Table 5) [4,8,9].…”
Section: Observations and Analysismentioning
confidence: 99%
“…This was probably due to interrupted technique of fascia closure, in which if any of suture was cut through, rest of sutures retained the fascia in opposition. Delayed absorbable and non-absorbable sutures were comparable in terms of incisional hernia incidence because PDS sutures loosed half of their mechanical strength in about 3 weeks and complete degradation took place in around 6 months, thus providing wound support for longer periods and reducing the chances of hernia formation (Table 6) [4,6,[9][10][11]. In nylon group, stitch granuloma rate was found to be 3.3% as compared to 0% in PDS group.…”
Section: Observations and Analysismentioning
confidence: 99%